Empirical investigation of the challenges of the existing tools used in global software development projects. Issue 5 (1st October 2015) - Niazi, Mahmood; Mahmood, Sajjad; Alshayeb, Mohammad; Hroub, Ayman
Abstract : Global software development (GSD) is continuously increasing because of many factors such as high quality software production in offshore destinations with significant cost‐savings. Objective – The objective of this study is to identify the challenges of the existing tools used in GSD projects. Method – The authors applied the systematic literature review (SLR) approach and a survey‐based empirical study approach to address the research objective. Results – From both data sets, the authors identified eight challenges of the existing tools used in GSD projects. The top‐ranked challenges in the SLR are the 'inappropriate use of synchronous and asynchronous communication tools' and 'difficulties in adopting and learning to use the existing tools'. The top‐ranked challenges in the questionnaire‐based empirical study are the 'lack of awareness of existing tools used in GSD projects' and the 'lack of support for collaboration and group decision making'. The results show a weak negative correlation between the ranks obtained from the SLR and the questionnaire‐based empirical study ((rs (8) = −0.313), p = 0.450) Conclusion: GSD organisations should address the challenges of the existing tools used in GSD projects, especially the most common ones.